On the completeness of algebraic polynomials in the spaces L_p (ℝ, dμ) - Bakan, A. G. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We prove that the theorem on the incompleteness of polynomials in the space C^0_w established by de Branges in 1959 is not true for the space L_p (ℝ, dμ)) if the support of the measure μ is sufficiently dense